Use of Tea Production Factors on Bedakah Plantation Unit PT Perkebunan Tambi Wonosobo Central Java: Analysis of Local Efficiency - Nada Qurrotul 'Aisy; Dwi Aulia Puspitaningrum; Budiarto Budiarto (Departement of Socio-Economic Agricuture, Faculty of Agriculture, 2021)
The research aims to 1) assess the impact of raw materials, wood pellets, fire woods, and electrical energy on black tea production at PT Perkebunan Tambi's Bedakah Plantation Unit tea factory, and 2) assess the level of allocative efficiency of the utility of black tea production factors at PT Perkebunan Tambi's Bedakah Plantation Unit tea factory. The descriptive technique is used with the case study implementation method in this study. Purposive sampling was used by the responders. Primary and secondary data were collected during a three-year period (2017-2019). For production factor analysis and allocative efficiency of production factors analysis, the analytical technique employs Cobb-Douglas, which calculates the ratio between the Marginal Value Product (MVP) and the input price (Px). The findings of this study revealed that 1) the number of raw materials and fire woods had an impact on the production of black tea at the Bedakah Plantation Unit tea factory, and 2) the utility of production factors in the form of raw materials and fire woods at the Bedakah Plantation Unit tea factory was ineffective. It is suggested that raw materials and firewood elements be added to the black tea processing at Bedakah Plantation Unit in order to attain aloocative efficiency.